Retention of learned predator recognition in embryonic and juvenile rainbow trout. (6th July 2019) - Horn, Marianna E; Ferrari, Maud C O; Chivers, Douglas P
Abstract: Minimizing predation risk, especially for young or naïve individuals, can be achieved by learning to recognize predators. Embryonic learning may optimize survival by allowing for the earliest possible response to predation threats posthatch. However, predatory threats often change over an individual's lifetime, and using old information can be detrimental if it becomes outdated. Adaptive forgetting allows an individual to discount obsolete information in decision-making and instead emphasize newer, more relevant information when responding to predation threats. Little is known about the extent to which young individuals can learn and forget information about predation threats. Here we demonstrate that rainbow trout 1) are capable of learning from both conspecific and heterospecific alarm cues as embryos, newly hatched larvae, and free-swimming larvae, 2) exhibit adaptive forgetting of predator information at all stages, and 3) display dynamic adaptive forgetting based on the ontogeny of learning. Specifically, fish that learned information as embryos retained the information for longer periods than those that learned the same information as newly hatched alevins. Abstract : It is well established that animals retain information for different periods of time, but the factors impacting retention are not well understood. Here, we explore the role of age in the retention of learned predator recognition by examining rainbow trout at three different early life stages. Timing of learning impacted information retention, such that embryos retained information longer than newly hatched conspecifics.